Strategi Pengembangan dan Analisis Kelayakan Usaha Pada PT XYZ (Studi Kasus : Tenant Badan Riset Inovasi Nasional) - Yuanto, Eka Novah; Raharja, Sapta; Aminah, Mimin (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2024)
PT XYZ is a company engaged in footwear/shoes, innovative products in the form of aromatherapy shoes equipped with essential oil extracts from orange peel waste which are useful to suppress the growth of bacteria that cause foot odor. Currently PT XYZ is receiving support from the government through a business incubatror institution, in the form of coaching to increase sales value supported by facilities and access to technology. The objectives of this study are (1) to identify internal and external factors that affect business development; (2) to analyze the business feasibility of PT XYZ; (3) to determine priority strategies for business development. The methods used in this research are SWOT analysis and Analytical Hierarchy Process. While business feasibility uses the calculation method of Payback Period, Net Present Value, Internal Rate of Return, Break Even Points. Internal factors that become strengths are always innovative to new products that are in demand by the market, while weaknesses are complicated recording of expenses and income. The external factor that becomes an opportunity is that as a tenant BRIN can use the lab and the threat is the theft of aromatherapy ideas. The business feasibility analysis is considered feasible and the results of the Determination of strategic priorities with AHP produce four strategic priorities